Profil Kemampuan Berpikir Kreatif Siswa pada Materi Perubahan Lingkungan - Wijayanti, Widha; Harlita, Harlita; Sugiharto, Bowo (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the initial profile of students' creative thinking on environmental change material in class X SMA Negeri I Purwantoro. This research is a descriptive qualitative research. The research sample was class X4 students totaling 33 students who were determined by purposive sampling technique. The research instrument used was a creative thinking ability test in the form of essay questions. Data analysis used descriptive quantitative. The results showed that the average creative thinking ability of students with a percentage of 38.75% and the category was less creative. The percentage for each aspect of students' creative thinking skills is in the fluency aspect of 41% with a fairly creative category, flexibility of 38% with a less creative category, originality of 39% with a less creative category, and elaboration of 36% with a less creative category. Thus, it can be concluded that the creative thinking skills of students in class X SMAN 1 Purwantoro are generally in the less creative category.